PENGARUH IKLAN, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN ALAT KESEHATAN (ORTOPEDI) PT. ADISKA SARANA MEDIKA DI DENPASAR - I Putu Eka Kurniadi; Ni Luh Putu Agustini Karta (Universitas Triatma Mulya, 2020)
This study aims to analyze the effect of advertising, brand image and service quality n purchasing decisions for medical devices (orthopedics) at PT. Adiska Sarana Medika. The sample analysis technique used purposive sampling method, where the sample is a customer of PT. Adiska Sarana Medika, as many as 80 people. The analysis technique used is to use Multiple Regression Analysis, which has previously been tested for validity, reliability test and classical assumption test. The results of the analysis show that 1) Advertising has a positive and significant effect on the decision to purchase medical devices (orthopedics) at PT. Adiska Sarana Media. 2) Brand image has a positive and significant effect on purchasing decisions for medical devices (orthopedics) at PT. Adiska Sarana Media; 3) Service quality has a positive and significant effect on purchasing decisions for medical devices (orthopedics) at PT. Adiska Sarana Media; and 4) Advertising, brand image and< service quality have a positive and significant effect on purchasing decisions for medical devices (orthopedics) at PT. Adiska Sarana Media. The implication in this research is that PT. Adiska Sarana Media needs to improve advertising, brand >image and service quality in an effort to improve purchasing decisions.